2020
DOI: 10.1371/journal.pone.0228205
|View full text |Cite
|
Sign up to set email alerts
|

Water consumption and prevalence of irritable bowel syndrome among adults

Abstract: Background and aimNo previous study examined the association between whole-day water intake and odds of irritable bowel syndrome (IBS). We examined the association between whole-day water intake and odds of IBS in a large sample of Iranian adults. MethodsThis cross-sectional study was conducted among 4763 adults in Isfahan, Iran. Daily water intake was assessed using a pre-tested questionnaire by asking questions about the average number of glasses of water consumed in a day. IBS was assessed and defined using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
1
4
1
Order By: Relevance
“…From our study, we noticed a significant relationship between IBS and depression, as well as we noticed a significant relationship between daily water intake and IBS. This finding is not so consistent with another study where an insignificant association was found between whole‐day water consumption and odds of IBS among the adult population 22 . From the analysis of our survey data, we found that 118 respondents had active IBS, and among them, the most predominant (54.2%) category of IBS was IBS‐C.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…From our study, we noticed a significant relationship between IBS and depression, as well as we noticed a significant relationship between daily water intake and IBS. This finding is not so consistent with another study where an insignificant association was found between whole‐day water consumption and odds of IBS among the adult population 22 . From the analysis of our survey data, we found that 118 respondents had active IBS, and among them, the most predominant (54.2%) category of IBS was IBS‐C.…”
Section: Discussioncontrasting
confidence: 78%
“…This finding is not so consistent with another study where an insignificant association was found between whole‐day water consumption and odds of IBS among the adult population. 22 From the analysis of our survey data, we found that 118 respondents had active IBS, and among them, the most predominant (54.2%) category of IBS was IBS‐C. Our study result depicts a variation with a recently published US population‐based survey where 37.3% of patients were diagnosed with IBS‐C.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…In contrast, Salari-Moghaddam et al (2020) reported a double risk of having irritable bowel syndrome among those who drank eight glasses or more water/day compared with those who drank two glasses or less. On the other hand, our casuistry failed to see an association between water consumption and IBS diagnosis; it is also important to note that these authors found no difference between water intake between women and men [ 49 ]. Furthermore, in the work by Zaribaf et al, it was found that those who drink many fluids during, before, or after meals have a lower risk of developing a functional bowel disorder [ 50 ].…”
Section: Discussionmentioning
confidence: 79%
“…The related problems in the questionnaire are strictly formulated according to the criteria to improve the accuracy of IBS diagnosis. Furthermore, many researchers use self-reported questionnaires to evaluate IBS, demonstrating the high reliability of the diagnostic results of this method [ 56 , 57 , 58 ]. Sixth, we cannot identify people with more than one eating style now, but we will work to overcome this challenge in the next step of our research.…”
Section: Discussionmentioning
confidence: 99%